Importance of the agar-media in the evaluation of bacteriocin activity against the same test-microorganisms - Pamela Oliveira de Souza de Azevedo (Brazilian Journal of Pharmaceutical Sciences, 2018)
Abstract Bacteriocins are peptides produced by various species of bacteria, especially lactic acid bacteria, which exhibit a large spectrum of action against spoilage bacteria and foodborne pathogens. Successful application of techniques for quantitative or qualitative bacteriocin determination relies not only on the sensitivity of the test-microorganisms, but also on the agar-medium employed. Cell free supernatants are routinely used to preliminary screen for antimicrobial activity of bacteria by means of the agar well diffusion method, but the supernatant may also include other molecules (such as medium components and/or intracellular compounds) accidentally released during cell free supernatant preparation, which may interfere with the assay. Reproducibility of bacteriocin activity against the same test-microorganisms is an important factor to be considered. Unfortunately, no specific information about bioassays standardization to determine bacteriocin activity is available in the literature. In this work, growth inhibition by means of the agar well diffusion assays were carried out on different agar-media showing a strong dependence on the agar-medium used, indicating that the inhibitory effects could also depend on the diffusion of exudates that are included in the cell-free supernatant. The results presented in this communication show that selection of the agar-medium is crucial for the bioassay response.